Portraying Cicero in Literature, Culture, and Politics From Ancient to Modern Times - Berno, Francesca Romana; La Bua, Giuseppe (CICERO - STUDIES ROMAN THOUGHT RECEPTION OA, 2022)
Cicero's self-portrait as master of Roman prose, philosopher, and statesman has often attracted interest from intellectuals over the times. This volume concentrates on the multiple ways by which different ages created their 'Ciceros'. An international group of scholars elaborates on the portrait of Cicero, contributing greatly to our understanding of the influence of the republican orator and politician on Western culture throughout the centuries.